2022
DOI: 10.7759/cureus.27481
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Mineral Density of Jaws With Skeletal Bone and Its Effect on Implant Stability in Osteoporotic Patients: A Review of Patient-Based Studies

Abstract: Osteoporosis has been an enigma in terms of the administration of implant therapy. It has been implicated as a cause of implant failure as it directly affects the quality of the bone. The diagnosis of osteoporosis is mainly done by measuring skeletal bone mineral density (BMD). During implant therapy, the BMD of jaws can be evaluated on routine orthopantomogram (OPG) or cone beam CT (CBCT). The various advantages of CBCT include establishing a correlation between skeletal bone density and bone density of jaws … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
0
5
0
6
Order By: Relevance
“…These results were in accord with the previous studies. Pisulkar and colleagues 65 stated that implant success was dependent on implant stability, which had a direct relationship with the regional bone quality. The finite element analysis of Sugiura and colleagues 30 in 2018 found that the density of cancellous bone had a significant impact on the micro motion of implant, reducing the cantilever can effectively reduce the maximum micro motion of implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in accord with the previous studies. Pisulkar and colleagues 65 stated that implant success was dependent on implant stability, which had a direct relationship with the regional bone quality. The finite element analysis of Sugiura and colleagues 30 in 2018 found that the density of cancellous bone had a significant impact on the micro motion of implant, reducing the cantilever can effectively reduce the maximum micro motion of implant.…”
Section: Discussionmentioning
confidence: 99%
“…These results were in accord with the previous studies. Pisulkar and colleagues 65 stated that implant success was dependent on implant stability, which had a direct relationship with the regional bone quality.…”
Section: Patient With Class IV Bone Had Lower Mbl In All-on-6 Groupmentioning
confidence: 99%
“…However, the relationship between skeletal and mandibular or maxillary bone density is limited and inconsistent 56,57 . Indeed, some authors have found a weak evidence to establish that regional bone density could be a useful parameter in predicting primary implant stability and at the same time a useful indicator of skeletal BMD 56,58 …”
Section: Osteoporosismentioning
confidence: 99%
“…За останніми даними остеопороз зареєстрований у 75 мільйонів людей у США, країнах Європи та Японії разом узятих -це кожна третя жінка у постменопаузальному періоді та майже половина всіх чоловіків та жінок віком 50 років [2]. Остеопороз -системне захворювання скелета, що характеризується зниженням маси кістки в одиниці об'єму та порушенням мікроархітектоніки кісткової тканини, що призводять до збільшення крихкості кісток та ризику їх переломів від мінімальної травми або навіть без такої [3]. Остеопороз (ОП), за даними Всесвітньої організації охорони здоров'я, посідає четверте місце серед інших захворювань, поширених на Землі, поступаючись лише хворобам серцево-судинної системи, онкологічним та ендокринним [4].…”
Section: активність маркерів кісткового метаболізму у тварин зі змоде...unclassified
“…Кісткова тканина щелеп за будовою та хімічним складом мало чим відрізняється від інших кісток скелета [1,4]. Однак в альвеолярній кістці процеси внутрішньої перебудови протікають активніше, ніж у інших кістках скелета [3]. У нормі висота альвеолярного гребня підтримується фізіологічною рівновагою між формуванням і резорбцією кістки, які регулюються не тільки системними, а й місцевими факторами [5].…”
Section: активність маркерів кісткового метаболізму у тварин зі змоде...unclassified